Synthesis of Melamine Core Starburst Polyamide G1 Dendrimer and its Antibacterial and Antioxidant Activities - Balu, Periyasamy; Viswambaran Asharani, Indira; Thirumalai, Dhakshamurthy (Asian Journal of Chemistry, 2020)
A novel polyamide first-generation dendrimer 7 was synthesized from new methodology under mild reaction conditions. The AB2 adduct, ethyl 2-[N-[2,2-bis(hydroxymethyl)propionyl]amino]ethylate (3), was prepared from 2,2-bis(hydroxymethyl)propionic acid (bis-MPA) and glycine as a linker. Further, G1 dendrimer 7 was synthesized by coupling melamine (5) with monomer 3. The structural elucidations of all the compounds were confirmed by FTIR, 1H & 13C NMR and HRMS. The G1 dendrimer was found to exhibit significant antibacterial activity against S. aureus and E. cloacae and antioxidant activity by DPPH scavenging method when compared to the standard, ascorbic acid.